Self esteem enhancement among youth with disabilities - Aina Razlin, Mohammad Roose; Rafidah Aga, Mohd Jaladin; Janet Ann, Fernandez (Penerbit Universiti Malaya, 2022)
Numerous studies have shown that self-esteem can affect people with disabilities in various ways. The role of self esteem is undeniably significant, to help people with disabilities pursue their lives successfully. This chapter discussed about self esteem among people with disabilities, the model of self esteem, causes of low self esteem among people with disabilities, characteristics of low self esteem, impacts of low self-esteem, and the interventions for low self esteem.